Developing intercultural communication competence of international students as Indonesian tourism promotion agents - Turistiati, Ade Tuti; Suebsook, Khwanchanok; Karunia, Zahra Dwi; Lutfiana, Anisa (Manajemen Komunikasi, 2026)
Background: As temporary residents, international students in Indonesia frequently engage in everyday intercultural interactions with local communities. These interactions not only shape their intercultural communication competence (ICC) but also position them as informal ambassadors who can promote Indonesian culture and tourism through their daily experiences and digital narratives. Building on the concept of ICC proposed by Brian H. Spitzberg, this study explores how intercultural engagement among international students contributes to the informal promotion of Indonesian tourism. Purpose: This research aims to examine how international students construct and develop their ICC through engagement with Indonesian culture and how these experiences indirectly promote Indonesian tourism, particularly through social media practices. Methods: The study employs a phenomenological approach to understand the lived experiences of 13 international students from Thailand, the Philippines, Tajikistan, Yemen, Sudan, Libya, the Gambia, and Cambodia who are studying in Indonesia. Data were collected through interviews, observation, and analysis of the students’ social media content, including posts, images, and narratives that reflect their cultural interactions and communication practices. The analysis focuses on how experiential cultural learning and relational cultural negotiation shape their intercultural communication processes. Results: The results reveal that international students develop ICC through continuous adaptation to their social environment. They adjust their verbal and nonverbal communication styles to align with local cultural expectations and audience preferences. Through social media storytelling and visual documentation, they share experiences of Indonesian culture, traditions, and tourist destinations, thereby promoting Indonesian tourism informally to their global networks. However, challenges remain in linguistic adaptation, particularly in mastering Indonesian and local languages such as Javanese. Conclusions: Intercultural engagement enables international students to develop their ICC. This study extends Spitzberg’s ICC framework by highlighting international students’ role as informal tourism promoters. Implications: This research suggests collaborative initiatives among universities, government tourism authorities, and private tourism stakeholders to strategically involve international students in broader tourism promotion programs.